Effect of Prenatal Zinc Supplementation on Birthweight - Saaka, Mahama; Oosthuizen, Jacques; Beatty, Shelly (Journal of Health, Population and Nutrition, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Although iron and zinc deficiencies are known to occur together and also appear to be high in Ghana, a few supplementation studies addressed this concurrently in pregnancy. In a double-blind, randomized controlled trial, 600 pregnant women in Ghana were randomly assigned to receive either a combined supplement of 40 mg of zinc as zinc gluconate and 40 mg of iron as ferrous sulphate or 40 mg of elemental iron as ferrous sulphate. Overall, there was no detectable difference in the mean birthweight between the study groups, although the effect of iron-zinc supplementation on the mean birthweight was masked by a strong interaction between the type of supplement and the iron status of participants [F (1,179)=5.614, p=0.019]. Prenatal iron-zinc supplementation was effective in increasing the mean birthweight among anaemic and iron-deficient women but not among women with elevated iron stores in early pregnancy. J Health Popul Nutr 2009 Oct; 27(5):619-631